2018
DOI: 10.1111/bpa.12647
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal susceptibility to beta‐amyloid toxicity and ischemic injury involves histone deacetylase‐2 regulation of endophilin‐B1

Abstract: Histone deacetylases (HDACs) catalyze acetyl group removal from histone proteins, leading to altered chromatin structure and gene expression. HDAC2 is highly expressed in adult brain, and HDAC2 levels are elevated in Alzheimer's disease (AD) brain. We previously reported that neuron-specific splice isoforms of Endophilin-B1 (Endo-B1) promote neuronal survival, but are reduced in human AD brain and mouse models of AD and stroke. Here, we demonstrate that HDAC2 suppresses Endo-B1 expression. HDAC2 knockdown or k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 43 publications
(133 reference statements)
2
24
0
Order By: Relevance
“…The importance of methylation in aging is linked with another epigenetic modification, histone acetylation (Zeng et al, 2015; Wang et al, 2018). A global reduction in gene expression, referred to as an epigenetic blockade, is observed in AD and may be regulated by post-translational modifications of histones (Gräff et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of methylation in aging is linked with another epigenetic modification, histone acetylation (Zeng et al, 2015; Wang et al, 2018). A global reduction in gene expression, referred to as an epigenetic blockade, is observed in AD and may be regulated by post-translational modifications of histones (Gräff et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9] Mitochondrial dysfunction appears to contribute to ischemic stroke by increasing oxidative stress, perturbing calcium homeostasis and inducing neuronal apoptosis. 10 correspondence: Jianfeng Zhang Oxygen and glucose deprivation (OGD), one of the most important pathogenic mechanisms in cerebral infarction, 11 is widely used in vitro as a model of ischemic stroke. OGD induces oxidative stress and formation of ROS, which damage cerebral neurons.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work demonstrates a role for HDAC2 in regulation of mitochondrial dynamics in primary mouse cortical neurons [13]. While class I HDACs, HDAC 1 and HDAC2, are required for neuronal specification from neural progenitor cells [20] and control synapse function and maturation [8] in mice, HDAC2 expression and regulation of cellular processes in living, human neurons has not yet been examined.…”
Section: Expression Of Hdac2 and Endophilin-b1 (Endo-b1) Isoforms In mentioning
confidence: 99%
“…We observed that HDAC2 protein expression is present at all time points but levels decline as neuronal differentiation proceeds ( Figure 1B, C). Our previous work in mouse primary cortical neurons demonstrated that HDAC2 expression negatively impacts the expression of Endophilin-B1 (Endo-B1), a multifunctional protein involved in mitochondrial dynamics [13]. In neurons, Endo-B1 is alternatively spliced yielding neuron-specific Endo-B1b and Endo-B1c as major isoforms relative to the ubiquitously expressed Endo-B1a [26].…”
Section: Expression Of Hdac2 and Endophilin-b1 (Endo-b1) Isoforms In mentioning
confidence: 99%
See 1 more Smart Citation